Identification, Intervention and Collaboration: The Keys To Working Successfully With Mildly Handicapped Students In Rural Areas - Dean K. McIntosh; Gail I. Raymond (Educational Considerations, 1989)
As the nation's schools are moving toward integration of mild-to-moderate handicapped students within general education classrooms, teachers must gain additional skills and expertise in both diagnosis and remediation.